Epidemiology of colic syndrome in horses over 15 years of care - Nardi, Larissa Tonelli [UNESP]; Ortega, Beatriz Tereza; Santos, Rafaela Silveira; Garcia, Raphael Borges; Cholfe, Bruno Fornitano (Editora da Universidade Federal Rural do Semi-Arido - EdUFERSA, 2020)
Colic syndrome is a condition of great importance in equine production, a syndrome considered to be complex and multifactorial in nature. In this way epidemiological studies have been acting to contribute to the identification of risk factors in the development of wind power. This study evaluated the clinical epidemiology of the colic syndrome according to race, gender, diagnosis, affected segment, therapeutic decision and outcome of the cases treated at the Veterinary Hospital Dr Halim Atique, interior of São Paulo. The medical records of the animals assisted from January 2004 to July 2018, whose complaint was abdominal discomfort, were evaluated. Of the 535 animals, the most affected breed was the Quarter Horses (69.3%) followed by the Mangalarga (6.9%); females (53.1%) were more prone to the development of the syndrome. Compaction (28.8%), gastritis (11.8%), followed by gas distension (10.3%) were the most frequent changes; the affected segments being the stomach (21.9%), major colon (17.2%), and small intestine (15.7%). Clinical treatment (64.7%) was the most instituted and in the outcome of the cases, the discharge (77.4%) prevailed. The study presents data that can support epidemiological research in the area, assisting in the identification of causal and predictive factors for the colic syndrome.
Epidemiologia da síndrome cólica em equinos ao longo de 15 anos de atendimento
Keywords: Acute abdomen; Compaction; Gastroenterology; Quarter horse